Disorder‐to‐order transition in PE–PPE proteins of Mycobacterium tuberculosis augments the pro‐pathogen immune response. Issue 1 (17th December 2019) - Ahmad, Javeed; Khubaib, Mohd; Sheikh, Javaid Ahmad; Pancsa, Rita; Kumar, Saroj; Srinivasan, Alagiri; Babu, Mohan Madan; Hasnain, Seyed E.; Ehtesham, Nasreen Z.
Abstract : A growing body of evidence supports the hypothesis that intrinsically disordered proteins often mediate host–pathogen interactions and modulate host functions for pathogen survival and virulence. Mycobacterium tuberculosis ( M.tb ) has evolved largely through reductive evolution, with a few exceptions such as the glycine–alanine‐rich PE–PPE/PGRS protein family, which has been expanding in pathogenic mycobacteria. Here, our analyses of the M.tb proteome and secretome revealed that the PE–PGRS subfamily is enriched for disordered regions and disordered binding sites, pointing to their importance in host–pathogen interactions. As a case study, the secondary structure of PE35–PPE68 and PE32–PPE65 of the pathogenesis‐related RD1 and RD8 regions was analyzed through Fourier‐transform infrared spectroscopy. These disordered proteins displayed a considerable structural shift from disordered to ordered while engaged in the formation of complexes. While these proteins are immunogenic individually and enhance the pro‐pathogen response, their corresponding complexes enhanced the responses manifold as displayed here by PE35 and PPE68. It is likely that M.tb exploits such disorder–order structural dynamics as a strategy to mount a pro‐pathogen response and subvert host defense for productive infection. This functional gain also serves as a means to compensate genomic content loss due to reductive evolution. Abstract : Mycobacterium tuberculosis exploits disordered proteins to subvert the host immune response. Bioinformatic analysis of various protein families of M. tuberculosis revealed that PE/PPE–PGRS family proteins are highly disordered and interact with cognate partners to achieve ordered structure as validated by FTIR. Immunization of mice indicated that the ordered protein complex exhibits gain of function by augmenting the immune response compared to that produced against disordered proteins.